BAD PUBLIC LEADERSHIP IN SOUTH AFRICA: THE JACKIE SELEBI CASE - Schwella, Erwin (Scientia Militaria - South African Journal of Military Studies, 2013)
This article scrutinises the literature on bad public leadership and then presents an analysis of a South African case of bad public leadership. Leadership is analysed in terms of contextual as well as conceptual perspectives. The article emphasises that both context as well as conceptual and theoretical factors should be considered when analysing the emergence, manifestation and maintenance of bad public leadership. In this sense, the article speaks to both precipitating as well as predisposing issues as factors in causing and sustaining bad public leadership. The literature is then applied to the rise and the subsequent demise of Jackie Selebi, erstwhile National Commissioner of the South African Police Service and President of Interpol, as a case study of bad public leadership.